Paramilitary Territorial Control and Patterns of Violence Against Civilians in Colombia: Disappearances in a Stable Paramilitary Fiefdom - Gutiérrez Sanín, Francisco (PARTECIPAZIONE E CONFLITTO, 2022)
The article looks at territorial control in a paramilitary fiefdom in Colombia, through the lens of a specific form of violence against civilians: disappearance. It finds that the outcomes and micro-dynamics governing disappearance can hardly be explained plausibly through some of the core ideas found in the literature of rebel governance. It explains why this is so, and proposes alternative conceptualizations.